Studies in chronic allergic bronchopulmonary aspergillosis. 4. Comparison with a group of asthmatics. Issue 3 (June 1977) - Malo, J L; Inouye, T; Hawkins, R; Simon, G; Turner-Warwick, M; Pepys, J
Abstract : A comparison is made of lung function tests and radiographic findings in 20 asthmatic patients with allergic bronchopulmonary aspergillosis paired in terms of sex, age, and duration of asthma with 20 other asthmatics in whom the diagnosis of aspergillosis was excluded in order to see if the aspergillosis causes more lung damage. One hundred per cent of the patients with aspergillosis and 75% of the patients with asthma alone showed a significantly reduced forced expiratory volume in one second (FEV1) before bronchodilator. All the patients in the two groups had a significantly reduced maximal expiratory flow at 50% vital capacity breathing air (V50air) but the severity of the reduction was statistically greater in the aspergillosis group. Reversibility in FEV1 of 15% and more was found in 50% of patients with asthma alone as against 31% of patients with aspergillosis. The degree of reversibility of FEV1 was also statistically greater in patients with asthma alone. Improvement of less than 20% of V50 after helium-oxygen breathing was found in 33% of the patients with asthma alone and in 75% of the patients with aspergillosis. Patients with aspergillosis also showed significantly (0-001 less than P less than 0-01) more reduced gas transfer factor. Radiological features of overinflation were as common in the two groups. Tubular and ring shadows were found in 95% and 60% respectively of patients with aspergillosis as against 45% and 15% of patients with asthma alone.